REGULATORY DOCUMENTS ON ENHANCING THE INFLUENCE AND NATIONALITY OF THE UZBEK LANGUAGE - Khamrayev Fozilbek Yuldoshevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, attention is paid to the development of the Uzbek language, the issues of its nationality, graphic and lexical problems that exist in the Uzbek language in different periods, and the efforts aimed at their solution are highlighted. Also, there was an opinion about the government's decisions on increasing the prestige of the Uzbek language as a state language and practical work aimed at ensuring their implementation.